LAWS AND PENALTIES FOR PERPETRATORS OF CHILD EXPLOITATION: CASE ANALYSIS AND IMPLICATIONS - FADLURRAHMAN YASUB (Yayasan Pendidikan Aksara Cendikia, 2026)
Child exploitation remains one of the most persistent violations of children's rights in Indonesia, threatening the physical, psychological, and social development of the nation's youngest citizens. This study examines the legal framework and criminal sanctions imposed on perpetrators of child exploitation in Indonesia, together with the broader implications of law enforcement, through an analysis of judicial decisions and the prevailing statutory regime, most notably Law Number 35 of 2014 on Child Protection. Employing a normative juridical method supported by case-study analysis of court rulings and a review of contemporary scholarship, the research finds that although the legal architecture has been substantially strengthened over the past decade extending from physical and sexual exploitation into online and financially facilitated forms of abuse the practical enforcement of these rules continues to be hampered by evidentiary difficulties, inter-agency fragmentation, and resource constraints (Nelson and Santoso 2025; Sofian 2025). The findings further indicate that economic hardship, weak inter-agency coordination, and the rapid expansion of digital financial services have created new vectors for exploitation that existing institutions are still struggling to address (Wahyu 2025; Putri 2024). The study concludes that meaningful protection of children requires not only the continued refinement of substantive criminal law but also a coordinated, technologically literate, and victim-centered approach to enforcement.